The Role of Social Media Instagram in the Travel Process: Evidence from Young People in Surabaya - Lydia Felicia Prasetya; Marcella Caroline Jaya; Sienny Thio (Petra International Journal of Business Studies, 2021)
This paper aims to examine the role of Instagram in the travel process of Surabaya’s young people. This process was divided into five stages namely: dreaming, planning, booking, experiencing and sharing. Quantitative descriptive was employed by distributing 200 questionnaires with the age ranging from 18 to 24. Qualitative method was also utilized by having in-depth interviews with five informants. The results have shown that Surabaya’s young people attach greatest role of Instagram on dreaming stage and the least role on booking stage. Youngsters are inspired after seeing posts (uploads) associated with travel on Instagram due to travel-related accounts they follow. This study has provided a preliminary investigation of travel process using Instagram and it should provide insights to travel agents, both offline and online to consider Instagram as a promotional media with the fact that Instagram plays an important role in the travel process amongst young people.